2005
DOI: 10.1037/0012-1649.41.6.885
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Early Head Start for 3-Year-Old Children and Their Parents: Lessons for Policy and Programs.

Abstract: Early Head Start, a federal program begun in 1995 for low-income pregnant women and families with infants and toddlers, was evaluated through a randomized trial of 3,001 families in 17 programs. Interviews with primary caregivers, child assessments, and observations of parent-child interactions were completed when children were 3 years old. Caregivers were diverse in race-ethnicity, language, and other characteristics. Regression-adjusted impact analyses showed that 3-year-old program children performed better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
267
1
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 599 publications
(290 citation statements)
references
References 56 publications
7
267
1
8
Order By: Relevance
“…As a result, the internal consistency for each measure used in this study cannot be reported. The study authors report that internal consistency for all the measures is 0.70 or greater, with the exception of the Home Observation for the Measure of Environment (HOME), which they report as being 0.69 (Love et al, 2005).…”
Section: Methodsmentioning
confidence: 96%
“…As a result, the internal consistency for each measure used in this study cannot be reported. The study authors report that internal consistency for all the measures is 0.70 or greater, with the exception of the Home Observation for the Measure of Environment (HOME), which they report as being 0.69 (Love et al, 2005).…”
Section: Methodsmentioning
confidence: 96%
“…Researchers suggest that parenting interventions are instrumental in preventing child maltreatment in low-and middle-income countries (Knerr, Gardner, and Cluver 2013 Black et al 1994;Duggan et al 1999;Gelfand et al 1996;Love et al 2005). …”
Section: Evidence That Parenting Programs Work When Implemented Wellmentioning
confidence: 99%
“…As Magnuson and Waldfogel (2005) note "only one-third of Head Start teachers hold fouryear college degrees, and experts worry that low pay and low levels of provider education constrain program quality" (172). Some disagree that all Head Start programs are ineffective (Love, et al 2005, Wilen 2003, Zero to Three 2005. In their policy brief, the Zero to Three Policy Center (2005) argues that Early Head Start is highly effective.…”
Section: Preschool and Childcarementioning
confidence: 99%
“…This program reaches out to families either in childcare centers that provide additional parenting education and home based visits, or through home visits and parent-child socialization activities (Love et al 2005). In a large, randomized trial of 3,001 families in 17 programs, Love et al (2005) found that Early Head Start had modest, but statistically significant positive impacts on infants' and toddlers' cognitive skills and on positive parenting behaviors, compared to the control group. They further found that the program sites that were most fully implemented earlier on had children who did better than in program sites that took longer be fully established.…”
Section: Social Capitalmentioning
confidence: 99%